Fuzzy Fractal-Fractional Derivative-Based Modelling and Analysis of Monkeypox Transmission (European Journal of Pure and Applied Mathematics, 2025)
This study investigates the transmission dynamics of monkeypox using a fuzzy fractal fractional-order mathematical model. The model incorporates fuzzy triangular numbers into both system parameters and initial conditions to effectively represent uncertainty in real-world epidemiological data. By employing fractal-fractional derivatives, the model captures memory and hereditary effects, providing a more accurate representation of disease progression. The mathematical analysis, supported by Ulam-Hyers stability and fixed-point theory, confirms the model’s reliability. Numerical simulation reveals the effects of changing the fractional order and uncertain inputs on the susceptible, exposed, infected, and recovered populations. The results underscore the enhanced comprehension of monkeypox spread and recovery provided by the combined effects of fractional dynamics and fuzziness and provide important insights for public health policy.
Keywords: Fuzzy values, Triangular Fuzzy number; Mathematical Model; Fractal Fractional Operator; Lipchitz Function; Ulam-Hyers stability